Approximation by Finite Potentials - Malyshev, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider an infinite system of point particles whose interaction is described by a stable two-body interaction potential ϕ of infinite range. A sequence of finite interaction potentials ϕ R pointwise convergent to ϕ as R → ∞ is introduced. It is shown that the corresponding sequence of correlation functions ρ R converges to ρ in the norm of the Ruelle space E ξ.